Trophic factors GDNF and BDNF improve function of retinal sheet transplants(☆) - Yang, Pamela B. (Exp Eye Res, 2010)
The aim of this study was to compare glial-derived neurotrophic factor (GDNF) treatment with brain-derived neurotrophic factor (BDNF) treatment of retinal transplants on restoration of visual responses in the superior colliculus (SC) of the S334ter line 3 rat model of rapid retinal degeneration (RD). RD rats (age 4–6 weeks) received subretinal transplants of intact sheets of fetal retina expressing the marker human placental alkaline phosphatase (hPAP). Experimental groups included: (1) untreated retinal sheet transplants, (2) GDNF-treated transplants, (3) BDNF-treated transplants, (4) none surgical, age-matched RD rats, (5) sham surgery RD controls, (6) progenitor cortex transplant RD controls, and (7) normal pigmented rat controls. At 2–8 months after transplantation, multi-unit visual responses were recorded from the SC using a 40 ms full-field stimulus (−5.9 to +1 log cd/m(2)) after overnight dark-adaptation. Responses were analyzed for light thresholds, spike counts, response latencies, and location within the SC. Transplants were grouped into laminated or rosetted (more disorganized) transplants based on histological analysis. Visual stimulation of control RD rats evoked no responses. In RD rats with retinal transplants, a small area of the SC corresponding to the position of the transplant in the host retina, responded to light stimulation between −4.5 and −0.08 log cd/m(2), whereas the light threshold of normal rats was at or below −5 log cd/m(2) all over the SC. Overall, responses in the SC in rats with laminated transplants had lower response thresholds and were distributed over a wider area than rats with rosetted transplants. BDNF treatment improved responses (spike counts, light thresholds and responsive areas) of rats with laminated transplants whereas GDNF treatment improved responses from rats with both laminated and rosetted (more disorganized) transplants. In conclusion, treatment of retinal transplants with GDNF and BDNF improved the restoration of visual responses in RD rats; and GDNF appears to exert greater overall restoration than BDNF.